Karakteristik Pendidikan Keluarga dalam Perspektif Al-Qur'an dan Hadis - zuhri, Sholahuddin; Ratnasari, Dwi (Jurnal Ragam Pengabdian, 2026)
The family is the first and most fundamental educational institution, providing children with their earliest learning experiences before they enter formal education. It plays a crucial role in developing moral values, religious understanding, intellectual abilities, emotional maturity, and character. This study examines the characteristics of family education from the perspective of the Qur'an and Hadith using a library research approach with qualitative content analysis. The findings indicate that Islamic family education is a lifelong process beginning before birth and continuing throughout human life, encompassing the stages of conception, prenatal development, and postnatal upbringing. The Qur'anic parable of the good tree in Surah Ibrahim (14:24–25) reflects three essential characteristics of Islamic family education: strengthening aqidah as its foundation, providing beneficial knowledge to foster intellectual growth, and cultivating noble character together with positive social relationships. These characteristics contribute to the development of shalih and shalihah children who possess strong faith, broad knowledge, exemplary character, and the ability to face contemporary challenges while remaining committed to Islamic values.